The Protein, Peptide and Free Amino - Acid Contents of Some Species of Gracilaria from South-East Coast of India - Lewis, E J (Fishery Technology, 1964)
The Protein, Peptide and Free Amino - Acid Contents of Some Species of Gracilaria from South-East Coast of India